2011
DOI: 10.1111/j.1740-0929.2011.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of an α‐1, 3‐galactosyltransferase, an enzyme that creates xenotransplantation‐related α–Gal epitope, in pig preimplantation embryos

Abstract: α-1,3-Galactosyltransferase (α-GalT), an enzyme creating Galα1-3Gal (α-Gal) epitope on the cell surface in some mammalian species such as pigs, is known to be a key factor that causes hyperacute rejection upon transplantation from pigs to humans. To establish the RNA interference-based suppression of endogenous α-GalT messenger RNA (mRNA) synthesis in porcine preimplantation embryos, we determined the suitable embryonic stage at which stage such approach is possible by using the semi-quantitative RT-PCR (qRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The -Gal epitope is specifically recognizable by staining with the isolectin, BS-I-B 4 (IB4) [24,25]. We have previously described the expression of -Gal epitope in porcine embryos using quantitative reverse transcription (RT)-PCR and cytochemical staining with fluorophore-conjugated lectin, which showed that its expression was already observable in oocytes and their zona pellucida (ZP), likely because of maternally accumulated products [26]. -GalT mRNA (generated from the embryonic genome) is detectable throughout the embryonic cleavage stage and reaches peak expression during the blastocyst stage [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The -Gal epitope is specifically recognizable by staining with the isolectin, BS-I-B 4 (IB4) [24,25]. We have previously described the expression of -Gal epitope in porcine embryos using quantitative reverse transcription (RT)-PCR and cytochemical staining with fluorophore-conjugated lectin, which showed that its expression was already observable in oocytes and their zona pellucida (ZP), likely because of maternally accumulated products [26]. -GalT mRNA (generated from the embryonic genome) is detectable throughout the embryonic cleavage stage and reaches peak expression during the blastocyst stage [26].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described the expression of -Gal epitope in porcine embryos using quantitative reverse transcription (RT)-PCR and cytochemical staining with fluorophore-conjugated lectin, which showed that its expression was already observable in oocytes and their zona pellucida (ZP), likely because of maternally accumulated products [26]. -GalT mRNA (generated from the embryonic genome) is detectable throughout the embryonic cleavage stage and reaches peak expression during the blastocyst stage [26]. However, our previous experiment using -Gal epitope negative cells as a somatic cell nuclear transfer (SCNT) donor demonstrated that -Gal epitope expression detected by staining with a fluorophore-conjugated IB4 was almost diminished in both ZP and embryo itself in the SCNT-derived blastocysts [27], which suggested the disappearance of the accumulation of the maternally inherited -Gal epitope in the cytoplasm of embryo and ZP, during embryogenesis and up to the blastocyst stage.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be required to establish a single embryo-based assay for detecting such mutations at the protein and gene levels, which will enable researchers to test whether the CRISPR/Cas9-related components constructed are effective for inducing mutations in the target locus. Blastocysts, stages just prior to implantation, are appropriate materials to test this issue since they can successfully be used for PCR-based amplification for molecular biological analysis [ 38 , 39 ] and express many types of mRNAs, including α-1,3-galactosyltransferase (α-GalT) gene ( GGTA1 ) [ 40 ]. It takes seven days to obtain blastocysts after fertilization in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…According to Chi et al. , weak staining was seen in the zona pellucida (ZP) of some parthenogenetic blastocysts. Consistent with this report, we observed weak staining in the ZP of one embryo (arrow in b of Fig.…”
Section: Resultsmentioning
confidence: 99%